Maternal Plasma Concentrations of Per- and Polyfluoroalkyl Substances and Breastfeeding Duration in the Norwegian Mother and Child Cohort. Issue 3 (September 2018) - Rosen, Emma M.; Brantsæter, Anne Lise; Carroll, Rachel; Haug, Line S.; Singer, Alison B.; Zhao, Shanshan; Ferguson, Kelly K.
Abstract : Background: Per- and polyfluoroalkyl substances (PFASs) have been widely produced, many of them persist in the environment, and have been associated with various health effects. Previous studies have identified inverse associations between perfluorooctanoic acid (PFOA), perfluorooctane sulfonate (PFOS), and breastfeeding duration, but have been limited in investigation of other PFASs. Methods: We measured the associations between plasma concentrations of nine different PFASs and cessation of breastfeeding before 3 and 6 complete months using women from the Norwegian Mother and Child Cohort Study (MoBa). The study population includes 1716 primarily nulliparous women from two previous studies of MoBa participants, enrolled from 2003 to 2007. The association was measured using Cox proportional hazards model. Mixtures analyses were performed using Elastic net regularization to identify interactive effects and control for copollutant confounding. Results: Concentrations of PFASs in this population were lower than concentrations in the previous studies on this topic. We found associations between increasing concentrations of perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), perfluoroundecanoic acid (PFUnDA), and decreased breastfeeding cessation (increased duration). The strongest associations were seen between PFDA and PFUnDA and cessation before 3 months: (both hazard ratios = 0.73; 95% confidence intervals = 0.62, 0.86). In our population, the other PFASs appeared to be unassociated with breastfeeding cessation. The mixtures analyses identified meaningful interactions between PFUnDA:PFDA, perfluorohexane sulfonate (PFHXS):PFOA, and PFOA:PFOS. Conclusions: The identification of associations between previously unexamined PFASs concentrations and increased breastfeeding duration is novel and may be explained by differences in transplacental transfer rates. Abstract : Supplemental Digital Content is available in the text.